2014
DOI: 10.1002/gps.4204
|View full text |Cite
|
Sign up to set email alerts
|

Subsyndromal depression among older adults in the USA: prevalence, comorbidity, and risk for new‐onset psychiatric disorders in late life

Abstract: In addition to the 13.7% of US older adults with lifetime MDD, an additional 13.8% have lifetime SSD, which is not a formally recognized diagnosis. In addition to its high prevalence, SSD is associated with elevated rates of comorbid mood, anxiety, and personality disorders, as well as the development of a new-onset MDD and anxiety disorder. These results underscore the importance of dimensional approaches to assessing depressive symptoms in older persons, as diagnostic approaches that rely on rigorous categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 34 publications
0
71
0
1
Order By: Relevance
“…Individuals with MDD represent the severe end of that spectrum, but examining trajectories of depression in the entire population will likely result in a more accurate representation of the true underlying continuum of the disorder. From a public health standpoint, subclinical depressive symptoms are relevant both because they predict future clinical illness (Horwath, Johnson, Klerman, & Weissman, 1994; Laborde-Lahoz et al, 2015; Pietrzak et al, 2013) and because they themselves are associated with significant morbidity (Chachamovich, Fleck, Laidlaw, & Power, 2008; Kang, Eno Louden, Ricks, & Jones, 2015) and negative outcomes (Allen, Chango, Szwedo, & Schad, 2014; Grabovich, Lu, Tang, Tu, & Lyness, 2010). In addition, studies of depressive symptom trajectories in general population samples of children and adolescents can speak to the role of depressive symptoms in normal child/adolescent development, something that studies restricted to patient samples would be unable to do.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with MDD represent the severe end of that spectrum, but examining trajectories of depression in the entire population will likely result in a more accurate representation of the true underlying continuum of the disorder. From a public health standpoint, subclinical depressive symptoms are relevant both because they predict future clinical illness (Horwath, Johnson, Klerman, & Weissman, 1994; Laborde-Lahoz et al, 2015; Pietrzak et al, 2013) and because they themselves are associated with significant morbidity (Chachamovich, Fleck, Laidlaw, & Power, 2008; Kang, Eno Louden, Ricks, & Jones, 2015) and negative outcomes (Allen, Chango, Szwedo, & Schad, 2014; Grabovich, Lu, Tang, Tu, & Lyness, 2010). In addition, studies of depressive symptom trajectories in general population samples of children and adolescents can speak to the role of depressive symptoms in normal child/adolescent development, something that studies restricted to patient samples would be unable to do.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive disorders had greater comorbidity when bipolar [143,144] or “atypical”[145]. Disorders subtyped by full or partial criteria were met found that this did not affect comorbidity [52,146,147] or that those with partial criteria had intermediate likelihood of comorbidity [148,149], suggesting heterogeneity.…”
Section: Major Findingsmentioning
confidence: 99%
“…[3, 9] Furthermore, subsyndromal depressive symptoms confer a risk factor for new-onset mood disorders. [7, 10] However, in the literature, symptoms have received much less attention than a clinical diagnosis of MDD, and some have argued that subsyndromal depression in very old participants may be related to normal aging rather than pathology. [11] A recent study showed that depressive symptoms are associated with biomarkers of Alzheimer’s disease among cognitively normal elderly participants.…”
Section: Introductionmentioning
confidence: 99%
“…[12] In addition, investigators previously recommended dimensional approaches to assess subsyndromal depressive symptoms rather than categorical classifications. [10]…”
Section: Introductionmentioning
confidence: 99%